Singularidades na ontogênese das diferenças do desenvolvimento sexual: perspectivas da Medicina e da Psicologia - Tolloto, Gilce Helena Vaz (2020)
Introduction: Differences in Sex Development (DSD) are challenging for professionals in the fields of Psychology and Medicine, because in some situations it is not possible to identify sex at birth, and diagnosis is made during adolescence or adulthood. To question which sex one belongs to is one of the most stressful inner conflicts that a person can experience. Individuals who live with DSD, although they are at risk of developing tumors, cardiovascular disease, osteoporosis, depression among other comorbidities at an early age, have only been studied by some groups in relation to their sexual aspects that shape the issues of social constructions, considering them as biological variations. What groups and perspectives address DSD in the fields of Psychology and Medicine? What are the possible comorbidities and singularities that occur throughout life? Is preventive management possible? The aim of this research is to contribute to the analysis of groups that evaluate individuals living with DDS from the viewpoints of Psychology, Medicine and the prevention of possible physical and psychological comorbidities. Method: A systematic review of the international literature and of institutions focused on interventions in the fields of Psychology, Medicine and civil society groups with innovative perspectives-- LGBTI+. Although studies related to healthcare were widely found in medical articles and journals, studies in Psychology were rare, because they are located in publications linked to other fields, such as education, law and social studies. Subjective reports in this field with experiences of DSD individuals were included as part of the literature, not limited to parameters exclusively produced by specialists in the healthcare area. Thus, we address reflections that now emerge and the major issues and tensions in the fields of Medicine and Psychology, broadening the space for coherent actions that may contribute to the health, prevention and wellness of people living with DSD. Conclusion: Contemporary biology has demonstrated that the rigid binary model XX/XY in modern Genetics with the discovery of sex mutations in individuals living with DSD, is insufficient to determine who that person is as an “individual”, segregated and placed in a state of anonymity and invisibility in relation to the heteronormative sexual pattern. In conclusion, it is not physically and psychologically healthy to live with this existential identity crisis. The unique and irreplaceable character of each human being, that allows a continuous transformation of one’s personality to become a reality may be conquered with the fundamental support of Psychology. These subjects are individualized as humans who have a psychological profile and civic identity with biological singularities. Thus, no one, not the physician or the psychologist can tell the sexual identity of people living with DDS. Only these individuals have the capacity and perception to declare what they actually are with singularities that enrich life